The Impact of the Experience of Gamification Marketing Activities on the Dimensions of Brand Appeal: Focusing on the Role of Brand Value - Leila Mokhtari (University of Tehran, 2021)
Objective: Given the importance of gamification activities in online stores, successful online marketing strategies include finding different ways to increase brand appeal and brand value. The majority of the businesses apply gamification activities in order to achieve loyalty and desirable consumer behaviors; the managers in this area, however, have paid little attention to other possible outcomes of this concept. Since the previous studies have examined the effects of gamification activities in accordance with the behavioral outcomes such as customers’ loyalty and the brand-customer relationship, which is an important behavioral precondition, has not been addressed, the present study aimed to investigate the effects of gamification marketing activities on the dimensions of brand appeal from the customer-brand perspective based on the analysis on Digikala online store. Methodology: The present study is applied in terms of purpose and descriptive-survey in terms of data collection. The statistical population of this research included the customers of Digikala online store. Non-probability available sampling method was used for the selection of the participants. Based on Jackson’s formula, the sample size was estimated at 221. A questionnaire was used to collect data whose validity was confirmed through content validity and its reliability was confirmed using Cronbach’s alpha coefficient as well as combined reliability coefficient. Descriptive data analysis was performed using SPSS software and the hypothesis were tested based on structural equation modeling using SMARTPLS3 software. Findings: The results of the present study showed that the experience of gamification marketing activities has a significantly positive effect on functional value and hedonic value. Besides, hedonic value has a significantly positive effect on the obsessive as well as harmonious brand appeal. In addition, functional value has a significantly positive effect on harmonious brand appeal, but it does not have a significant effect on obsessive brand appeal. Conclusion: In addition to valuing the gaming and entertainment experience for the customers, gamification activities support the creation of a functional value as well. On the other hand, the gamification experience by the customers can create a feeling of pleasure, joy, and excitement while interacting with the company’s activities such as shopping or reviewing the website. Moreover, creating values such as efficiency and cost-effectiveness of goods or services can lead to a kind of appeal that emphasizes the desire for autonomous internalization of the brand in the individuals’ identity and is consistent with other customer activities. Besides, when customers experience the feelings of pleasure, joy, and excitement in the process of buying or interacting with the company, it leads to the formation of a sense of appeal which creates an obsession in interacting with the brand; thus, they would sometimes tend to buy things for no special reasons. Consequently, in the process of buying or interacting with the company, the customers might experience feelings of pleasure, joy, and excitement which lead to the formation of sense of appeal in them which is also in harmony with other aspects of their lives and is automatically internalized in their identity.